109 When Too Many Feed Additives Is Not a Sustainable Approach to Replacing Feed Antibiotics. (7th May 2021) - Bradley, Casey L; Rosero, David
Abstract: Due to consumer and regulatory demands swine producers are being ever more pressured to remove feed- and water-grade medications from their production systems. Consequently, there is an ever-growing list of feeding strategies and feed additives that indicate their value to maintain growth performance in diets void of antibiotics, leaving a confusing landscape for producers to navigate their options. Non-antibiotic feed additives, as reviewed by Liu et al. (2018), of options include acidifiers, minerals, prebiotics, direct fed microbials or yeast, nucleotides, and plant extracts. Furthermore, enzymes such as phytase and xylanase when fed to pigs have shown indirect benefits to not only performance but also livability. But within this landscape of research there has been little evidence to support synergies of these different feed additive types as an opportunity to replace antibiotics, while providing relatively little on the economic implications of different strategies. A commercial example of this was a study conducted in the Hanor System (Enid, OK USA) in which they conducted a 3 different feed additives that could benefit gut health of nursery pigs: organic acids, phytochemicals, and direct-fed microbials. Of the three different products tested, the phytochemical additive was the only product to demonstrate a profit above diets without the addition of feed additives. Furthermore, another study in the Hanor System evaluating antibiotic alternatives in the nursery period using pigs that were positive with PRRSv (1-7-4) found an increase in mortality and reduction in full value pigs when antibiotics were removed. However, the beta-glucan product demonstrated a positive response to both mortality and full-value pigs, yet still did not return to full profitability as the antibiotic fed pigs. In conclusion, further investigation into the synergies of different categories of feed additives is necessary to not only find the ideal balance of performance benefits but also profitability.